Особенности оказания бесплатной юридической помощи: опыт Китая (Journal of actual problems of jurisprudence, 2019)
This article discusses the characteristics and problems of providing free legal aid in China. «The Regulations on Legal Aid» accepted in 2003 disclose the content and the meaning of the act in development of legal protection of Chinese citizens.